1978
DOI: 10.1007/bf01260892
|View full text |Cite
|
Sign up to set email alerts
|

5?-Nucleotidase of microglial cells in the facial nucleus during axonal reaction

Abstract: Transection of the facial nerve causes proliferation of microglial cells in the facial nucleus. The miroglial cells can be seen in perineuronal and perivascular positions. A high activity of 5'-nucleotidase is demonstrated cytochemically in the plasma membranes of these cells. The increase of enzymatic sites for the production of adenosine during axonal reaction might be of functional significance for the regenerating motor neuron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

1979
1979
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(40 citation statements)
references
References 21 publications
3
35
0
2
Order By: Relevance
“…If the extracellular space in brain is assumed to be 20%, then brain adenosine concentration during ischemia observed in the present study would range between 6 X 10" 6 M and 2.7 x 10~5 M, which is within the vasoactive range found by Wahl and Kuschinsky (1976). Moreover, Kreutzberg and Barron (1978) have demonstrated that the astrocytic footpads that surround the blood vessels contain 5'-nucleotidase in the cell walL Thus, the enzyme that produces adenosine is in close proximity to the vessel wall, and the diffusion distance between the site of production and the vascular smooth muscle is small. VOL.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…If the extracellular space in brain is assumed to be 20%, then brain adenosine concentration during ischemia observed in the present study would range between 6 X 10" 6 M and 2.7 x 10~5 M, which is within the vasoactive range found by Wahl and Kuschinsky (1976). Moreover, Kreutzberg and Barron (1978) have demonstrated that the astrocytic footpads that surround the blood vessels contain 5'-nucleotidase in the cell walL Thus, the enzyme that produces adenosine is in close proximity to the vessel wall, and the diffusion distance between the site of production and the vascular smooth muscle is small. VOL.…”
Section: Discussionsupporting
confidence: 64%
“…The location and factors affecting 5'-nucleotidase in brain have not been established as clearly as those in heart. However, in brain, this enzyme also is located in the cell wall (Kreutzberg and Barron, 1978) and appears in vivo to be greatly suppressed (Kluge et al, 1972;Arch and Newsholme, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Study of different injury models suggests that the type of injury determines the type of inflammatory cell present. For example, penetrating wounds of the brain contain both macrophage and activated microglia (Rio-Hortega, 1932;Ling, 198 1;Giulian, 1987), while axotomized cranial nerves contain only microglia (Kreutzberg and Barron, 1978). Both classes of brain mononuclear phagocyte, blood-borne macrophage and ameboid microglia, have been found to release IL-l (Giulian andBaker, 1985, 1986;Giulian, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…U CNS-u, e-5NT je opisan kao marker oligodendrocita [164][165][166], astrocita i aktivirane mikroglije [165][166][167]. U nezrelim neuronima, e-5NT je eksprimirana tokom razvića [168].…”
Section: Ekto-5'-nukleotidaza (E-5nt Cd73)unclassified
“…Ovo je posebno važno naglastiti, jer je izraženo mišljenje da je distribucija ovog enzima u centralnom nervnom sistemu pretežno vezana za gliju [165,166,168] te da je ekspresija e-5NT na kortikalnim neuronima niska [105,159].…”
Section: Ekspresija I ćElijska Distribucija Ent1 I Ent2unclassified